PENGARUH PERSEPSI KONSUMEN TERHADAP KUALITAS PELAYANAN PADA PT. ANGKASA PURA I BANDAR UDARA INTERNASIONAL SAM RATULANGI MANADO - Paulus, Adelweis G.P.; Rasjid, Efendy (MANAJEMEN ADMINISTRASI BISNIS DAN PEMASARAN, 2024)
PT. Angkasa Pura I Sam Ratulangi Manado International Airport is a company engaged in airport services under the leadership of General Manager, Minggus ET Gandeguai. The purpose of this study is to determine the Influence of Consumer Perceptions on Service Quality The type of research is quantitative research and research methods use Descriptive research methods with Consumer Perception as an independent variable and Service Quality as a dependent variable. The users of the service in question are unknown but the sample involved was 36 respondents using the Non Probability Sampling technique, namely Purposive Sampling. While the data analysis used is Descriptive Statistical Analysis, Total Score, Correlation Analysis and Simple Linear Regression. The results of the correlation coefficient value analysis shows that Consumer Perception has a strong and significant relationship with improving the Quality of Service From the results of the analysis of the answers The total score of the respondents, shows that the Quality of Service is categorized as good with a value of 74.13% but still needs to be improved because there is still a gap of 25.87%. The results of the analysis show that Consumer Perception has a significant influence on improving service quality at PT. Angkasa Pura I Sam Ratulangi International Airport Manado. For this reason, Consumer Perceptions need to be considered so that they can improve Service Quality